PERAN PENYULUH PERTANIAN DALAM PENGGUNAAN PUPUK ORGANIK DI PROVINSI KALIMANTAN SELATAN - Andi Suci Anita; Purna Kusumayana (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
Information dissemination through agricultural extension workers can increase knowledge, can change behavior, and attitudes of farmers, especially regarding the use of organic fertilizers. Changes in behavior and attitudes can be seen from the participation of farmers in using organic fertilizers. Participation through the participation of farmers can be a more efficient way to achieve the stated goals. The aim of this study was to examine the role of agricultural extension agents in the use of organic fertilizers in the Province of South Kalimantan. Measurement of the role of agricultural extension agents in the use of organic fertilizer using the median score. The role of agricultural extension agents in the use of organic fertilizers includes: the role of agricultural extension agents as motivators, mediators and supervisors. The role of agricultural extension agents as motivators in the use of organic fertilizers gets a median score of 4, which means that agricultural instructors are eager to encourage farmers to use organic fertilizers due to a fairly good farmer response so that extension workers can motivate farmers to use organic fertilizer. The role of agricultural extension agents as mediators in the use of organic fertilizers gets a median score of 4, meaning that the tasks of agricultural extension agents as mediators have been carried out well. Information or policies from related government or extension agencies are delivered by extension agents to farmers, both through regular meetings and incidental meetings. While the role of agricultural extension agents as supervisors in the use of organic fertilizers has a median score of 5 which means that the role of agricultural extension agents has been carried out to the maximum seen from the frequency of implementation of guidance by extension agents.